ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR - William, Thio Lie Sha (Jurnal Paradigma Akuntansi, 2020)
This study aims to prove empirically about the effect of profitability, liquidity, leverage, and firm growth on dividend policy on manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2016-2018. Sampling using a purposive sampling method that obtained 39 samples of manufacturing companies. The data used are secondary data in the form of financial information from financial statements. This research data processing uses the IBM SPSS STATISTICS 24 program. F test results profitability, liquidity, leverage, and firm growth together have a significant influence on the dividend policy. The result of t test show that profitability has a positive and significant influence on dividend policy. Meanwhile, liquidity and firm growth have a negative and significant effect on dividend policy. Leverage has no significant effect on dividend policy.